Pemberdayaan Warga Krukut Depok untuk Pencegahan Stunting melalui Pelatihan Pembuatan Cookies BROCA (Brokoli, Wortel, dan Ayam) - Tatiana Siregar; Ritanti Ritanti; Diah Ratnawati (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2026)
Background: Stunting remains a public health problem in Depok City, including the Krukut Subdistrict, while community understanding of stunting prevention and the use of local nutritious food ingredients remains limited. This community service program aimed to improve mothers’ knowledge of stunting prevention and strengthen their skills in producing healthy snacks for toddlers, specifically BROCA cookies made from broccoli, carrots, and chicken. Methods: The program involved 30 women from Majelis Ta’lim Ar-Rahman, RW 01 Krukut. Activities included health education, basic anthropometry training, demonstrations of BROCA cookie preparation, and discussions on home-scale production and marketing. Evaluation was carried out using pre-test and post-test questionnaires covering knowledge of stunting, child feeding, parenting and care, and stunting prevention. Results: Participants’ understanding increased across all evaluated domains, with statistically significant pre- to post-intervention differences (p=0.001). Conclusion: This program indicates that community-based education combined with practical food processing training has the potential to support stunting prevention efforts and encourage household-scale economic empowerment.